Navigating Utopian Waters: Dreams, Power, and Consequences in Ursula K. Le Guin’s The Lathe of Heaven and Octavia E. Butler’s “The Book of Martha” - Matilde Ribeiro Cameira, (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
ABSTRACT: This article aims to delve into the thematic intersections of Ursula K. Le Guin’s The Lathe of Heaven and Octavia E. Butler’s “The Book of Martha”, within the realms of dreams and their importance for utopianism. To achieve this goal, crucial and relevant scenes in both works are analysed and compared against each other. Firstly, there is an exploration of the fact that the existence of a perfect world for everyone is impossible. Secondly, it scrutinizes how each narrative grapples with the ethical and moral implications of wielding extraordinary power. Thirdly, it reflects on the characters’ agency and free will. Lastly, it examines how the characters deal with the consequences of their actions as well as their sense of guilt. Other aspects are also explored such as race, utilitarianism, and the ambiguity of utopia.